HUBUNGAN ANTARA KEIKUTSERTAAN DALAM PROGRAM PENGEMBANGAN DAN KINERJA PROFESIONAL GURU - Rukmana, Rita Aprilianti (Universitas Negeri Malang, 2017)
Abstract: This study aims to determine the relationship between participation in thedevelopment and professional performanceof vocational high school teacher in MalangCity. This research using a quantitative correlation approach. the data was analyzed usingProduct Moment Pearson correlation. The findings show that: (1) participation teachersin the development program in the category often with the average score of 97.87; (2)the performance variables of teacher professional included in the medium category withan average score of 107.48 so included in the enough professional category; and (3) therevariable correlation participation in program development and professional performance witha 0.366 correlation value is greater than 0,113. Thus it can be interpreted as the relationshipbetween Participation in the Program Development and Professional Teachers Performance.Keywords: Development programme, Performance, Profesional teachersAbstrak: Penelitian ini bertujuan untuk mengetahui hubungan antara keikutsertaan dalamprogram pengembangan dan kinerja profesional guru SMKN se-Kota Malang. Penelitianini menggunakan pendekatan kuantitatif korelasional. Data yang terkumpul dianalisismenggunakan uji korelasi Product Moment Pearson. Temuan penelitian menunjukkan,bahwa: (1) keikutsertaan guru dalam program pengembangan dalam kategori sering denganskor rata-rata sebesar 97,87; (2) variabel kinerja profesional guru masukdalam kategorisedang dengan skor rata-rata 107,48 sehingga termasuk dalam kategori cukup profesional;dan (3) terdapat korelasi variabel keikutsertaan dalam program pengembangan dan kinerjaprofesional dengan nilai korelasi 0,366 lebih besar dari 0,113.Dengan demikian dapatdimaknai adanya hubungan antara Keikutsertaan dalam Program Pengembangan dan KinerjaProfesional Guru.Kata kunci: Program pengembangan, Kinerja, Profesional guru. DOI: https://doi.org10.17977/um025v1i22017p107